Revitalisasi Kelompok Wanita Tani (KWT) melalui Pemanfaatan Pekarangan Rumah di Desa Metesih Kecamatan Jiwan Kabupaten Madiun - Amal Taufiq; Habib.R (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2018)
Farmer Women Groups (KWT/Kelompok Wanita Tani) is one of the organizations in Metesih Village, Jiwan Sub-District, Madiun Regency, East Java, KWT is present in the community to mobilize assets. When students arrived in the village, KWT was empty towards a leadership transition, after students carried out asset mapping, they found many assets, one of the most significant was an organization called KWT. All components of the community agreed to revitalize KWT with its revitalization main program, because by revitalization of KWT helping to strengthen the role of women in people live who had been considered weak, women could not find economic income for their families, with the strengthening of KWT role everything had changed. ABCD (Asset Based Community Development) was used in this research, because this approach was in accordance with the character of the community. Finally, the results obtained from this process namely changing in community mindsets, strengthening the role of KWT in community, increasing the role of women in various sectors and increasing community economic income from corn harvest in their fields.